Antidiabetic Effects of Soluble Dietary Fiber from Steam Explosion-Modified Black Soybean Hull in Low-Dose Streptozotocin-Induced Type 2 Diabetic Mouses - Meng Shen; Weihao Wang; Yunfei Ge; Ziyue Kang; Juan Wang; Zhigang Quan; Jinling Xiao; Longkui Cao (Journal of Chemistry)
This paper studies the antidiabetic effects of soluble dietary fiber (SDF) from steam explosion-modified black soybean hull in low-dose streptozotocin- (STZ-) induced type 2 diabetic mouses. Male C57/BL6 mouses were divided into 4 groups: control (nondiabetic, no SDF intake), model (diabetes only), metformin (metformin: 100 mg/kg body weight), and SDF (SDF: 600 mg/kg body weight). Four weeks post-SDF treatment, treatment of SDF decreased the weight gain of diabetic mouses, normalised the blood glucose level, and reduced the serum cholesterol, serum insulin, leptin, glucagon-like peptide, total cholesterol, triglyceride, low-density lipoprotein cholesterol, arteriosclerosis index, aspartate aminotransferase activity, and malondialdehyde. It also increased high-density lipoprotein cholesterol, adiponectin, glycopeptide peroxidase, superoxide dismutase activity and repaired the pancreatic injury of the diabetic mouses. Our research results show that SDF has the potential for use in type 2 diabetes treatment.